A 4.2-to-5.4 GHz stacked GaAs HBT power amplifier for C-band applications. Issue 4 (31st March 2020) - Liu, Min; Xu, Panpan; Zhang, Jincan; Liu, Bo; Zhang, Liwen
Abstract : Purpose: Power amplifiers (PAs) play an important role in wireless communications because they dominate system performance. High-linearity broadband PAs are of great value for potential use in multi-band system implementation. The purpose of this paper is to present a cascode power amplifier architecture to achieve high power and high efficiency requirements for 4.2∼5.4 GHz applications. Design/methodology/approach: A common emitter (CE) configuration with a stacked common base configuration of heterojunction bipolar transistor (HBT) is used to achieve high power. T -type matching network is used as input matching network. To increase the bandwidth, the output matching networks are implemented using the two L -networks. Findings: By using the proposed method, the stacked PA demonstrates a maximum saturated output power of 26.2 dBm, a compact chip size of 1.17 × 0.59 mm 2 and a maximum power-added efficiency of 46.3 per cent. The PA shows a wideband small signal gain with less than 3 dB variation over working frequency. The saturated output power of the proposed PA is higher than 25 dBm between 4.2 and 5.4 GHz. Originality/value: The technology adopted for the design of the 4.2-to-5.4 GHz stacked PA is the 2- µ m gallium arsenide HBT process. Based on the proposed method, a better power performance of 3 dB improvement can be achieved as compared with the conventional CE or common-source amplifier because of high output stacking impedance.